Combining Electrochemiluminescence Detection with Aptamer‐Gated Indicator Releasing Mesoporous Nanoparticles Enables ppt Sensitivity for Strip‐Based Rapid Tests. Issue 50 (9th November 2021) - Climent, Estela; Rurack, Knut
Abstract: The combination of electrogenerated chemiluminescence (ECL) and aptamer‐gated indicator delivering (gAID) magnetic mesoporous silica nanoparticles embedded into glass fibre paper functionalised with poly(ethyleneglycol) and N ‐(3‐triethoxysilylpropyl)diethanolamine allowed the development of a rapid test that detects penicillin directly in diluted milk down to 50±9 ppt in <5 min. Covalent attachment of the aptamer "cap" to the silica scaffold enabled pore closure through non‐covalent electrostatic interactions with surface amino groups, while binding of penicillin led to a folding‐up of the aptamer thus releasing the ECL reporter Ru(bpy)3 2+ previously loaded into the material and letting it be detected after lateral flow by a smartphone camera upon electrochemical excitation with a screen printed electrode inserted into a 3D‐printed holder. The approach is simple, generic and presents advantages with respect to sensitivity, measurement uncertainty and robustness compared with conventional fluorescence or electrochemical detection, especially for point‐of‐need analyses of challenging matrices and analytes at ultra‐trace levels. Abstract : The best of both worlds in one strip, i.e., electrochemical excitation and luminescence emission, together with aptamer‐gated hybrid nanomaterials enables the detection of penicillin directly in milk at ultra‐trace levels in less than 5 min with a simple test strip and a mobile communication device.